Editor’s foreword - Radaev, Vadim (Journal of Economic Sociology, 2019)
Dear Colleagues, We introduced a new rubric, “Discussions,” some time ago with some doubts regarding the viability of this venture. However, it has gone quite well so far. In this issue, we have begun publishing the authors’ responses to their critics. We received two substantive replies from Roman Bumagin and Dmitry Rogozin on the critical response to their paper. Rostislav Kapelyushnikov has also submitted an extended reply to one of our recently published critical essays on the legacy of Max Weber. This reply will be prepared for the next issue.